Moses in Corinth the apologetic context of 2 Corinthians 3 - Duff, Paul B. 1952- (Boston Brill, 2015)
In Moses in Corinth , Paul Duff contends that the imagery focused on Moses in 2 Corinthians 3 functions as an integral part of Paul's apologia , a defense created by the apostle to refute suspicions about his honesty and integrity
1. Introduction.The problematic nature of 2 Corinthians 32.The question of the integrity of 2 Corinthians3.The origins of Paul's first apology4."Who is fit for these things?" (2 Cor 2:14-3:6)5.The ministries of condemnation and righteousness (2 Cor 3:7-11)6.Not like Moses? (2 Cor 3:12-18)7 Reading Paul reading Moses.
Includes bibliographical references and index. - Print version record
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Moses -- Biblical teaching; Moses -- (Biblical leader) -- Biblical teaching; Moses; Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible. Corinthians, 2nd, III -- Criticism, interpretation, etc; MOSES (Biblical leader) -- Biblical teaching; RELIGION ; Biblical Studies ; New Testament; RELIGION ; Biblical Studies ; Paul's Letters; Biblical teaching; Criticism, interpretation, etc; Electronic books